Interdigitated Ambipolar Active Layer for Organic Phototransistor with Balanced Charge Transport. (13th February 2019) - Jeong, Uijin; Tarsoly, Gergely; Lee, Junghyun; Eun, Youngmoo; Do, Junghwan; Pyo, Seungmoon
Abstract: The formation and characterization of interdigitated ambipolar active layers prepared by a hybrid (solution processing and thermal vacuum evaporation) method for a polymer‐gated organic phototransistor with highly balanced ambipolar charge transport is reported. The interdigitated active layer is comprised of a solution‐processed single‐crystalline microcrystal array of p‐type 6, 13‐bis(triisopropylsilylethynyl)pentacene (TIPS‐pentacene) and a thin film of n‐type N, N ′‐ditridecylperylene‐3, 4, 9, 10‐tetracarboxylic diimide (PTCDI‐C13 ). The TIPS‐pentacene single‐crystalline microcrystal, which is confirmed using X‐ray diffractometry and polarized optical microscopy, is embedded in the PTCDI‐C13 film deposited using a thermal vacuum evaporation method. The devices with the interdigitated active layer exhibit selective charge transport characteristics varying from unipolar to ambipolar depending on the thickness of the PTCDI‐C13 film. The fabricated ambipolar organic transistor shows high photoresponsivity at low light intensities and good dynamic photoresponse. These results demonstrate the potential use of such devices in ambipolar optoelectronic applications. Abstract : Organic phototransistors with p‐ and n‐type interdigitated semiconductors layer are fabricated. The electrical characteristics of the devices vary from unipolar to ambipolar depending on the composition of the interdigitated layer. The fabricated ambipolar device shows well‐balanced charge transport and high photoresponsivity at low light intensities.